Which factors support trust in the recommendation process of pension products? Trust and pension products - Philip Maximilian Linhart; Olaf Stotz (Journal of Financial Services Marketing, 2021)
During the financial crisis of 2008/2009, financial institutions such as banks and insurance companies have lost trust of their customers. In the recommendation process of pension products, trust plays an important role since cash flows from retirement products accrue decades ahead. Using the results from a survey, we find that financial institutions still struggle to deliver trust to their customers when they recommend different categories of retirement products. Other recommending parties such as academic financial experts or close friends, however, are able to establish a high level of trust. We therefore investigate factors of alternative channels to establish trust such as the recommendation process or product features.
Keywords: 330; Pension products; Trust; Financial literacy